Ask questions and get helpful answers.
Ask a New Question

Suppose you wish to express sin(3t) in terms of sint and cost. Apply the sum formula to sin(3t) = sin(t+2t) to obtain an expression that contains sin(2t)=sin(t+t) and cos(2t)=cos(t+t). Apply the sum formulas to those two expressions. Enter the resulting expression for sin(3t) here:____

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩

1 answer

  1. sin(3t) = sin(2t)cos t + sint cos(2t)
    = [2sint*cos^2t + sint(cos^2t - sin^2t)
    = 3sint*cos^2t -sin^3t
    You can get rid of the cosine function.
    = 3sint(1 - sin^2t)- sin^3t
    = 3sint -4 sin^3t

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.